APLIKASI KOAGULAN CAIR HASIL EKSTRAKSI 0,4 MOL H2SO 4 UNTUK PENGOLAHAN AIR GAMBUT - Catrain Susanty; Muhdarina '; Akmal Mukhtar (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Clay is an abundant natural product that has  been used  in various fields, one of them as a    coagulant in water treatment. Cengar clay contains  aluminium and iron that can be extracted to be liquid coagulant. The liquid coagulant was prepared through extraction of  500o C calcined  Cengar clay  by 0,4 mol  of sulfuric acid at  various temperatures  (30,60,  and 100o C) and extraction times  (1,  2,  and 3 hours).  These coagulants were  applied to coagulation process of peat water. Several  parameters  of peat water  that were analyzed are  turbidity, total dissolve solid  (TDS),  and  total suspended solid  (TSS). The turbidity  result was compared to  PERMENKES RI No.  416/MENKES/PER/IX/1990 “About Requirement and Water Quality Control”,  whereas  TDS and TSS  were compared to  Government Regulation No. 82 of 2001  “About Water Quality Treatment and Water Pollution Control” class  I (raw drinking water). The result showed that liquid coagulants  can  fix  all of  peat water  parameters that  were  analyzed.  The optimum coagulant was K 60-3,  made through extraction at  60o C  for 3 hours, with  removal percentage of turbidity was 82,69%; TSS 94,06%, and TDS 84,75%.